Complication Patterns of Loop Ileostomy (Delta Medical College Journal, 2024)
Background: Loop ileostomy is a temporary diversion of small intestinal contents towards exterior through anterior abdominal wall. Though it is a good procedure for a better outcome of primary surgery it has itself many complications. Objective: To determine the clinical spectrum of loop ileostomy complications. Materials and method: This prospective study was conducted from January, 2017 to December, 2017. Consecutive 30 patients requiring loop ileostomy were enrolled in the study by purposive sampling and were categorized into Group A requiring emergency surgery and Group B planned for elective surgery. Data regarding sociodemographic, clinical, surgical and outcome profile were recorded in a pre-structured, interview and observation based, peer reviewed data collection sheet. Data were compiled, edited and analyzed with SPSS version 23. Data were presented as mean and standard deviation, frequency percentage and median with range. Results: The mean age of the patients were 32.79±5.19 years (age range: 20-43 years) and 49.16±6.17 years (age range: 28-76 years) in Group A and Group B respectively with sex ratio of male to female of 4:1 and 3:1. Out of 10 patients in Group A, 4(40%) patients underwent resection anastomosis with ileostomy and primary repair with loop ileostomy whereas 2(20%) patients underwent exteriorization of multiple perforation site. In Group B among 20 patients, 9(45%) underwent low anterior resection with loop ileostomy and 5(25%) patients underwent left hemicolectomy with loop ileostomy. Out of 10 patients in Group A, 5(50%) patients each suffered from skin excoriation and major wound infection. On the contrary, among 20 patients in Group B, 11(55%) and 4(20%) patients suffered from skin excoriation and stomal obstruction. Only skin excoriation was evident as statistically significantly higher in Group B than in Group A (p 0.03). Among the general complications, electrolyte imbalance (60% vs 40% in Group A and B respectively) and respiratory tract infection (10% each in Group A and B) were evident. Conclusion: Skin discoloration, skin edema, major and minor wound infection, prolapse, skin excoriation and stomal obstruction are the different spectrum of loop ileostomy complications in our perspective. Among them skin excoriation is much higher in routine cases than emergency surgery.Delta Med Col J. Jan 2021;9(1):17-22